2016
DOI: 10.1093/bja/aev549
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine post-treatment induces neuroprotection via activation of extracellular signal-regulated kinase in rats with subarachnoid haemorrhage

Abstract: Dexmedetomidine post-treatment provides neuroprotection against SAH. This effect appears to be mediated by ERK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 36 publications
1
36
0
1
Order By: Relevance
“…Thus, the neuroprotection of dexmedetomidine from I/R‐induced injury to neuronal cells takes place via an anti‐apoptotic pathway. Recent studies reported that dexmedetomidine might have the potential at protection against experimental spinal cord injury and subarachnoid hemorrhage‐induced brain damage [Cosar et al, ; Gul et al, ; Wang et al, ]. In addition, dexmedetomidine could defend intestine, myocardial, renal, lung, cerebral and liver from reperfusion injury via an antiapoptotic pathway [Cai et al, ; Cui et al, ; Scott, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the neuroprotection of dexmedetomidine from I/R‐induced injury to neuronal cells takes place via an anti‐apoptotic pathway. Recent studies reported that dexmedetomidine might have the potential at protection against experimental spinal cord injury and subarachnoid hemorrhage‐induced brain damage [Cosar et al, ; Gul et al, ; Wang et al, ]. In addition, dexmedetomidine could defend intestine, myocardial, renal, lung, cerebral and liver from reperfusion injury via an antiapoptotic pathway [Cai et al, ; Cui et al, ; Scott, ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dexmedetomidine is received wide attraction because of its potential at neuroprotection. Accompanied by cerebral vasospasm, subarachnoid hemorrhage is a serious condition, and dexmedetomidine is shown to defend against subarachnoid hemorrhage‐induced brain injuries through activating mitogen‐activated protein kinases (MAPK) in rats [Cosar et al, ; Wang et al, ]. In addition, Gul et al [] reported the effectiveness of dexmedetomidine in experimental spinal cord injury.…”
mentioning
confidence: 99%
“…Dexmedetomidine is a highly selective α 2 -adrenoreceptor agonist with sedative, anxiolytic, and analgesic effects [14, 15]. It also exhibits neuroprotective properties [16], anti-inflammatory benefits [17], and protective effects on the myocardium [18], against ischemia or reperfusion in the brain [19], and against lung [20], kidney [21], and liver injuries [22, 23]. In patients undergoing percutaneous RFA of small HCCs under general anesthesia with sevoflurane, it is unclear whether dexmedetomidine exhibits outstanding advantages over remifentanil in terms of pain management, or if it could be an alternative to remifentanil.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the functional inactivation of RASSF1A results in failure of inhibiting effect on tumor cells. Researchers have detected the expression levels of p16 and RASSF1A mRNA in non-small cell lung carcinoma and found that their expression levels are distinctly down-regulated [6,7]. Therefore, blocking ERK signal pathway, down-regulating Dnmts and its protein expression levels, and up-regulating p16 and Ras mRNA and its protein expression levels can exert an inhibitory effect on the proliferation and growth of tumor cells.…”
Section: Discussionmentioning
confidence: 99%